Pengaruh Budaya Organisasi, Independensi, Objektivitas, Akuntabilitas, dan Pengalaman Kerja Pada Kinerja Pengawas LPD - Winarsih, Kadek Pipit; Suardana, I Ketut Alit (E-Jurnal Akuntansi, 2018)
The purpose of this research was to determine the effect of organizational culture, independence, objectivity, accountability, and work experiencein supervisory performance LPD in the Tampaksiring district Gianyar regency. The population of the research is the LPD that is still operating in the whole of Tampaksiring distric Gianyar regency. The sampling technique that used in this research is purposive sampling. Sample criteria used are LPD supervisors in Tampaksiring Distric who have occupied positions at least two years. The sample used in this reasearch is 32 LPD with total 96 of respondents. The research shows indpendensi and objectivity have a positive influence and no significant effect to the supervisory performance. In partially, accountability and work experience have significant and positive influence to the supervisory performance. However the organizational culture partially has negative influence and no significant effect to the supervisory performance LPD. Keywords : supervisor, performance, organizationalculture, independence, objectivity, accountability, and work experience